NILAI PERUSAHAAN DITINJAU DARI UKURAN PERUSAHAAN DAN KINERJA KEUANGAN DENGAN DIMEDIASI OLEH TEKNOLOGI INFORMASI - Muhammad Azis Aprian Afi Luqman; Suyatmin Waskito Adi (ITB AAS Indonesia Surakarta, 2025)
This research aims to analyze the influence of company size and financial performance on company value with information technology as a mediating variable in banking companies listed on the Indonesia Stock Exchange (BEI) for the 2021–2024 period. The research method used was a quantitative approach with a purposive sampling technique on 43 banking companies, producing 172 observation data which was processed using path analysis. The research results show that company size and financial performance have a significant positive effect on company value. Company size and financial performance also influence the level of information technology adoption, with the influence of company size being more dominant. Furthermore, information technology has a significant positive effect on company value, which indicates that the implementation of digital systems can increase efficiency, reputation and investor confidence. The results of the mediation test show that information technology mediates the relationship between company size and company value, but does not mediate the relationship between financial performance and company value. These findings confirm that digital technology adoption is an important factor in strengthening the relationship between organizational characteristics and the market value of banking companies. Keywords : company value, company size, financial performance, information technology, banking.